Barriers to male condom use in Rohingya refugee camps in Bangladesh: A qualitative study - M Mofizul Islam; Md Mashiur Rahman; Md Nuruzzaman Khan (Elsevier, 2022)
Summary: Background: Rohingya people are often called the most persecuted minority in the world. Currently, almost 800,000 Rohingya refugees live in temporary shelters in Cox's Bazar, Bangladesh. More than one-quarter of them are women and girls of reproductive age who are at increased risk of unplanned pregnancies, unsafe abortions and related complications. However, the use of contraception remains inadequate, and particularly use of condoms and male participation is scarce. This study examines the barriers to condom use as a contraceptive method among married Rohingya couples. Methods: We conducted in-depth qualitative interviews of married Rohingya men and women and thematically analysed the data. Findings: Depo Provera injections and pills are the dominant forms of contraception. Men's participation in family planning and contraceptive use is rare, and so is the use of condoms. Participants identified several barriers to condom use, including contraception being the responsibility of the women, socio-cultural issues, the stigma attached to condoms, unfamiliarity with condoms, the limitations of condoms, and issues of security in conjugal life. Health workers do not promote condoms in the same way as other contraceptive methods. Interpretation: Condom use and men's participation in contraception use are rare in Rohingya camps. The involvement of family planning workers who are males may help to promote the use of condoms and increase the method-mix options of contraceptives. Funding: La Trobe University, Melbourne, Australia.